Phenomenon of compensative and compulsive buying in Poland: A socio-economic study - Grzegorz Adamczyk (Economic and Environmental Studies (E&ES), 2018)
This article examines the phenomenon of compensative and compulsive buying in a consumer society such as Poland. The prevalence of compensative and compulsive buying in Poland is discussed in comparison with other countries. Sociodemographic conditions of compensative and compulsive buying such as age, gender, income, debts of households or class of locality size are analysed. An important goal of the theoretical part of the article is a presentation of different methods of measuring compensative and compulsive buying (e.g. Canadian Compulsive Buying Measurement Scale, German Addictive Buying Indicator, Compulsive Buying Scale, Edwards Compulsive Buying Scale). The empirical findings presented in the article come from two waves of surveys conducted in 2010 and 2016 based on a nation-wide statistically representative sample of 1,000 Poles. The presented results of these surveys based on the German Compulsive Buying Indicator. Currently 4.4% of Poles aged 15 years and older show susceptibility to compulsive buying. The share of the compensative buyers in the total population amounts to 16.1%.
Keywords: D12; E21; I12; M31; 330; consumer behaviour; compensative buying; compulsive buying; behavioural addiction